Representations of religion in the entertainment media: A comparison of the TV series Shtisel in Israel and Ömer in Türkiye - Ayşenur Kılıç (Connectist Istanbul University Journal of Communication Sciences)
This research focuses on two cases from the Global South -the Israeli series Shtisel and its Turkish scripted format adaptation Ömer- to revisit the theoretical debates on the relations between entertainment media, politics, and society by employing Curran’s radical democratic approach. Both series illustrate a recently popular genre: Pious people’s bemusement with modern/secular everyday life. Analyzing TV format adaptations in Türkiye is further significant because the imported format adaptations remain relatively less studied. Four main narratives come into prominence via the narrative analysis: i) the use of technology, ii) the skepticism towards the outside world in Ömer, iii) gender narratives, and iv) politicization/depoliticization of representations of religion. Shtisel represents religion without reflecting current socio-political conflicts, Ömer reflects religion as a site of contestation and polarization of differing identities by reproducing political conflicts from everyday life into fiction. Curran’s framework explains Ömer sufficiently but is limited in helping understand Shtisel unless the Israeli case’s transnational political-economic context is considered. Finally, to comprehend multilayered, dynamic, and sui generis cultural dimensions for each case in the Global South -which is not a homogenous whole- further theoretical inquiry on local, cultural and intertextual characteristics of scripted format adaptations in individual cases is needed.